Fabrication of Wood-Derived Carbon Aerogel/Mg(OH)2 Bio-Composite and Its High Performance for Adsorption and Separation of Cadmium Ions - Ran An; Jinyue Liu; Haomiao Ma; Yuqing Yan; Yuanru Guo; Qingjiang Pan; Shujun Li (C, 2025)
To address the need for reducing carbon emissions and enhancing the sustainable utilization of non-fossil resources, a one-step calcination strategy has been developed to fabricate hierarchical carbon aerogels from balsa wood. The resulting wood-derived carbon aerogels (WCA) were functionalized with Mg(OH)2 to boost their environmental remediation potential. Comprehensive characterization using XRD, FT-IR, XPS, and SEM confirmed that the optimized WCA/Mg(OH)2 composite (WCAMg) retained a three-dimensional hierarchical porous structure, and Mg(OH)2 nanosheets were attached to it. The adsorption performance of WCAMg composites towards Cd2+ was systematically investigated through controlled experiments, which focused on three critical variables (Mg(OH)2 loading content, initial Cd2+ concentration and solution ionic strength). The functionalized WCAMg demonstrated a maximum Cd2+ adsorption capacity of 351.1 mg g−1—a tenfold improvement over pristine WCA. Combined with exceptional adsorption efficiency, this biomass-derived composite offers an eco-friendly, cost-effective solution for heavy metal ion remediation. Its scalable fabrication from renewable resources aligns with sustainable water treatment objectives, presenting the advantage of pollution mitigation.